Relationship between age and some social-psychological factors in marriage. - Olaguer, Rhea Melissa L; Quimsing, Joyce D. (1999.)
This study was conducted to demonstrate how age at the time of marriage is related to some social-psychological variables that included perceived readiness for marriage, readiness for motherhood and childcare, level of marital satisfaction and perceived marital stability. The respondents were sixty (60) married mothers whose ages ranged from 18-40 years at present. The research setting was in Iloilo. The questionnaire was used to gather data. A rank-correlation statistic was used to analyze data. Results revealed that there is a significant and direct correlation between age at the time of marriage and the said variables
Thesis (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Married Mothers